Antibacterial Activity of Eucalyptus Camaldulensis Extracts on Staphylococcus aureus Isolated from Nasal Cavity - Zahraa Sedeeq Qasim; Farah Hazem Omer; Maimonah Qasim Yahya (Indian Journal of Forensic Medicine & Toxicology, 2021)
To study the effect of prepared Eucalyptus camaldulensis in aqueous, ethanol and flavonoid extracts byconducting susceptibility tests against Staphylococcus aureus isolated from nasal carrier of healthy subjects,in addition to detection some of virulence factors by conducting ?-lactamase enzyme test, and biofilmformation test. This study included 250 healthy subjects, the males were 125(50%) and 125(50%) females.Two swab samples were collected from each subject, the studied samples collected during one year periodfrom (April / 2018- April 2019). Different culture media and biochemical tests were used for isolationand identification the isolates as Staphyllococcus aureus, in addition to prepared three types of Eucalyptuscamaldulensis extracts in form of aqueous, ethanol and flavonoid. Susceptibility test was conduct by discdiffusion method, then study some of virulence factors of Staphyllococcus aureus by conducting ?-lactamaseenzyme test and biofilm formation test. Among 250 healthy subjects involved in this, study Staphyllococcusaureus 68 (27%) isolates were detected, isolates from male was 40 (59%), while from female was 28 (41%),only 39 (57 %) isolates were sensitive to different concentrations of Eucalyptus camaldulensis, of bothaqueous and ethanol extracts, ethanol extract had a higher effect on Staphyllococcus aureus than aqueousextract, while 45 (66%) isolates were sensitive to flavonoid extract. Twelve (18%) isolates form a biofilm intube method, and 48 (71%) isolates showed ?-lactamase test positive. A higher nasal carriage were in malesin this study than females. The anti Staphyllococcus aureus effect of Eucalyptus camaldulensis extractswere flavonoid followed by ethanol then aqueous extracts, some of Staphyllococcus aureus isolates werehighly virulence by showing a positive result for ?- lactamase enzyme and biofilm formation test. this studyshown that the flavonoid extract of E. camaldulensis have a great potential as antimicrobial agents on S.aureus than crude aqueous and ethanol extracts, many nasal pharmaceutical preparation can prepare fromE. camaldulensis in crude and flavonoid form for treatment infections and reduce nasal carrier of S. aureus.